Characterization of Thermally Sprayed Coated GT Components Made of 3D Printing Based Selective Laser Melting Processed Inconel Alloy 718 - Mohammed Yunus; Mohammad S. Alsoufi (International Journal of Aerospace Engineering)
Functional requirements like higher strength, resistance, and shielding from chemical reactions, degradation, etc., of the base metal are achieved by modifying their exposed surfaces using TBC (thermal barrier coating). Modified outer surface of components in the GT (gas turbine) improves the performance by the increase of inlet temperature, enhancing longer life and providing many interrelated surfaces to withstand severe working conditions. This work is based on characteristic (mechanical, thermal, and tribology) evaluation of TBC-coated GT components made of Inconel 718 manufactured from traditional and 3-D printing-based selective laser melting (SLM) process and compared. TBCs comprising bond coat and top ceramic oxide coat were deposited by High-Velocity Oxy-Fuel and Atmospheric Plasma Spraying techniques, respectively. Characteristics evaluated by varying coating thickness, standoff distance, substrate preheating, Input torch power, etc., revealed that characteristics of substrates manufactured from SLM methods improved significantly except porosity and average surface roughness. These improvements are essential for embedding sensors, thin films, etc., in TBCs for continuous monitoring of outputs.